Haematological And Biochemical Changes In Cattle Of Floor With Special Refference To Endosulfan - Jyotsana Menon (Department of Pharmacology and Toxicology, College of Veterinary and Animal Sciences, 2002)
A study was undertaken to assess the impact of environmental pollution with endosulfan in cattle of Eloor industrial belt. Hindustan Insecticide Limited is the major industrial unit handling endosulfan is situated here. So this area was selected for the conduct of study. Field samples like sludge, water and fodder and biological samples like blood, dung, urine and milk of cattle in the study area were collected. The collected samples were analysed for endosulfan level by gas liquid chromatography and compared (statistically) with those of control samples collected from University Livestock Farm (ULF), Mannuthy. A higher level of endosulfan could be detected in the field and biological samples ofEloor cattle than control animals. Milk samples collected from both Eloor area and ULF, Mannuthy had no detectable level of endosulfan in them except for one sample from the study area. Fodder was suspected to be the main source of endosulfan to cattle. A significant change was noticed in lymphocyte count, neutrophil and eosinophil count of the animals in affected area. Other haematologic values like total leucocyte count, total erythrocyte count, packed cell volume and erythrocyte indices (MC V, MCH, MCHC) did not show any significant di fferences. Eventhough the biochemical parameters like the creatinine